Fabrication of Poly(Glycerol Sebacate)-Poly(ε-Caprolactone) Extrusion-Based Scaffolds for Cartilage Regeneration - Reis, D. (2019)
Cartilage related diseases are on the top list concerns of the World Health Organization, being the prevention of articular cartilage degeneration a major health matter for which there are few effective solutions. Using an extrusion-based approach and a polyester elastomer it was aimed to produce 3D structures with controlled architecture and with closer mimicry to cartilage native tissue. The obtained constructs demonstrated high reliability, being the addition of poly (glycerol sebacate) a procedure to enhance the properties of the constructs.